ULTRASOUND COMPARISON IN DETERMINING THE TUMOUR SIZE OF BREAST CANCER BY TAKING PATHOLOGIC EXAMINATION AS GOLD STANDARD (The Research of Medical Science Review, 2024)
OBJECTIVE: To determine the accuracy of ultrasound in determining the tumour size by taking actual size of the tumour based on the results of the pathologic examination as gold standard in patient with breast cancer.METHODOLOGY: This cross-sectional study was carried out in the Department of Radiology SIUT Karachi from November 2022 to May 2023. The sample of 142 patients with age group 18–70 years diagnosed with breast cancer at any stage and undergoing surgical tumor resection were selected through non-probability consecutive sampling. Ultrasound examinations were performed by one of four board-certified radiologists with 4–15 years of experience in breast imaging, using either a 5–12 MHz transducer with an iU22 system (Philips Healthcare, Netherlands) or a 4–15 MHz transducer with an Aixplorer system (Super-Sonic Imagine, France). The tumor size was then assessed on pathologic examination after surgical resection of the tumor in all patients in order to assess the accuracy. The SPSS version 26.0 was used to analyze the data.RESULTS: The mean ± SD of age of the patients was 53.53± 10.65 years. A greater proportion of participants which accounted for (53.7%) were postmenopausal, with the remaining 46.3% being premenopausal. Accuracy rates were found to be similar in both age groups with 70.4% of participants over 50 years and 29.6% for those aged 18–50 years with insignificant difference (p=0.970). For DCIS impact on accuracy, higher accuracy was observed in subjects without DCIS than with DCIS (67.6% versus 32.4%) with insignificant difference (p = 0.057). CONCLUSION: Accurate tumor size assessment is vital for effective breast cancer management. While ultrasound is a valuable, non-invasive tool, its accuracy is influenced by tumor characteristics, operator expertise, and technical limitations. Advancements like three-dimensional ultrasonography and elastography show promise for improving precision, but standardization of imaging protocols remains essential. Refining ultrasound accuracy through technological innovations will enhance treatment planning and patient outcomes